Dyke to sill deflection in the shallow heterogeneous crust during glacier retreat: part I - Drymoni K.; Tibaldi A.; Bonali F. L.; Pasquare Mariotto F. (Bulletin of Volcanology, 2023)
Dykes and sills occupy Mode I (extension), Mode II (shear), or hybrid mode fractures and most of the time transport and store magma from deep reservoirs to the surface. Subject to their successful propagation, they feed volcanic eruptions. Yet, dykes and sills can also stall and become arrested as a result of the crust's heterogeneous and anisotropic characteristics. Dykes can become deflected at mechanical discontinuities to form sills, and vice versa. Although several studies have examined dyke propagation in heterogeneous and anisotropic crustal segments before, the conditions under which dykes propagate in glacial-volcanotectonic regimes remain unclear. Here, we coupled field observations with 2D FEM numerical modelling to explore the mechanical conditions that encourage (or not) dyke-sill transitions in volcanotectonic or glacial settings. We used as a field example the Stardalur cone sheet-laccolith system, which lies on the Esja peninsula, close to the western rift zone, NW of the southern part of the Icelandic rift. The laccolith is composed of several vertical dykes that transition into sills and form a unique stacked sill 'flower' structure. Here, we investigate whether the Stardalur laccolith was formed under the influence of stresses caused by glacial retreat due to thickness variations (0-1 km) in addition to regional and local tectonic stresses (1-3 MPa extension or compression) and varied magma overpressure (1-30 MPa), as well as the influence of the mechanical properties of the lava/hyaloclastite contact. Our results show that the observed field structure in non-glacial regimes was formed as a result of either the mechanical (Young's modulus) contrast of the lava/hyaloclastite contact or a compressional regime due to pre-existing dykes or faulting. In the glacial domain, the extensional stress field below the ice cap encouraged the formation of the laccolith as the glacier became thinner (subject to a lower vertical load). In all cases, the local stress field influenced dyke to sill deflection in ...